Electrophysiological determinant for induction of isthmus dependent counterclockwise and clockwise atrial flutter in humans. Issue 1 (1st January 1999) - Lin, J-L; Lai, L-P; Lin, L-J; Tseng, Y-Z; Lien, W-P; Huang, S K S
Abstract : Objective: To investigate the electrophysiological determinant underlying the electrical induction of counterclockwise and clockwise isthmus dependent atrial flutter. Patients and methods: The isthmus bordered by the inferior vena caval orifice–tricuspid annulus–coronary sinus ostium (IVCO–TA–CSO) has been assumed to be the site of both slow conduction and unidirectional block critical to the initiation of atrial flutter. Trans-isthmus and the global atrial conduction were studied in 25 patients with isthmus dependent atrial flutter (group A) and in 21 patients without atrial flutter (group B), by pacing at the coronary sinus ostium and the low lateral right atrium (LLRA) and mapping with a 20 pole Halo catheter in the right atrium. Results: Mean (SD) fluoroscopic isthmus length between the coronary sinus ostium and LLRA sites was 28.1 (4.0) mm in group A and 28.0 (3.9) mm in group B (p = 0.95), but the trans-isthmus conduction velocity of both directions at various pacing cycle lengths was nearly halved in group A compared with group B (mean 0.39–0.46 m/s v 0.83–0.89 m/s, p < 0.0001). Pacing at coronary sinus ostium directly induced counterclockwise atrial flutter in 14 patients and pacing at LLRA induced clockwise atrial flutter in 11 patients, following abrupt unidirectional trans-isthmus block. Transient atrial tachyarrhythmias preceded the onset of atrial flutter in 10 counterclockwise and six clockwise cases of atrial flutter. None of the group B patients had inducible atrial flutter even in the presence of trans-isthmus block. The intra- and interatrial conduction times, as well as the conduction velocities at the right atrial free wall and the septum, were similar and largely within the normal range in both groups. Conclusions: Critical slowing of the trans-IVCO−TA−CSO isthmus conduction, but not the unidirectional block or the global atrial performance, is the electrophysiological determinant of the induction of counterclockwise and clockwise isthmus dependent atrial flutter in man.